A Generalization for Theorems of Datko and Barbashin Type - Pham Viet Hai (Journal of Function Spaces)
The goal of the paper is to give some characterizations for the uniform exponential stability of evolution families by unifying the discrete-time versions of the Barbashin-type theorem and the Datko-type theorem.